miRNome Profiling and Functional Analysis Reveal Involvement of hsa‐miR‐1246 in Colon Adenoma‐Carcinoma Transition by Targeting AXIN2 and CFTR - Lukosevicius, Rokas; Juzenas, Simonas; Salteniene, Violeta; Kulokiene, Ugne; Aristikyte, Justina; Hemmrich‐stanisak, Georg; Franke, Andre; Link, Alexander; Ruzgys, Paulius; Satkauskas, Saulius; Pauzas, Henrikas; Latkauskas, Tadas; et al. (International Journal of Molecular Sciences, 2022)
Regulatory changes occurring early in colorectal cancer development remain poorly investigated. Since the majority of cases develop from polyps in the adenoma‐carcinoma transition, a search of early molecular features, such as aberrations in miRNA expression occurring prior to cancer development, would enable identification of potentially causal, rather than consequential, candidates in the progression of polyp to cancer. In the current study, by employing small RNA‐seq profiling of colon biopsy samples, we described differentially expressed miRNAs and their isoforms in the adenoma‐carcinoma transition. Analysis of healthy‐adenoma‐carcinoma sequence in an independent validation group enabled us to identify early deregulated miRNAs including hsa‐miR‐ 1246 and hsa‐miR‐215‐5p, the expressions of which are, respectively, gradually increasing and decreasing. Loss‐of‐function experiments revealed that inhibition of hsa‐miR‐1246 lead to reduced cell viability, colony formation, and migration rate, thereby indicating an oncogenic effect of this miRNA in vitro. Subsequent western blot and luciferase reporter assay provided evidence of hsamiR-1246 being involved in the regulation of target AXIN2 and CFTR genes’ expression. To conclude, the present study revealed possible involvement of hsa‐miR‐1246 in early colorectal cancer development and regulation of tumor suppressors AXIN2 and CFTR.
CRIS-Team Scopus Importer:2025-10-13
Keywords: Adenomatous polyps; Colorectal cancer; IsomiR; MicroRNA; Small RNA‐seq